Assessment of Different Lactic Acid Bacteria Isolated from Agro-Industrial Residues: First Report of the Potential Role of Weissella soli for Lactic Acid Production from Milk Whey - Montero Zamora, Jéssica Pamela (2022)
Abstract: The production of lactic acid (LA) through the microbial conversion of agro-industrial residuals is an important process in the biotechnology industry. The growth kinetics of 30 strains of lactic acid bacteria (LAB) isolated from agro-industrial residues were determined and nine strains were selected for microbioreactor fermentation. Lactiplantibacillus pentosus_70-1 (1.662) and L. pentosus_ 19-2 (1.563) showed the highest OD600 values, whereas the highest growth rates were observed for L. pentosus_19-2 (0.267 h−1) and Weissella soli_31 (0.256 h−1). The production of LA and acetic acid (AA), glucose consumption, and metabolic profiles were determined, without finding significant differences in the production of LA; however, W. soli_29 produced the highest amount of LA (20.833 gL−1) and was able to metabolize most of the studied carbohydrates. Based on these results, W. soli_29 was chosen for a 20 h fermentation in a 7 L bioreactor using both standard medium and milk whey supplemented medium. W. soli_29 produced 16.27 gL−1 and 7.21 gL−1 of LA in each of these mediums, respectively. These results show the underlying potential of Weissella strains for biotechnological applications. Additional analysis which should contemplate different agro-industrial residues and other conditions in bioreactors must be carried out.